Fermentative hydrogen production from mixed and pure microalgae biomass: Key challenges and possible opportunities. (19th October 2017) - Shobana, Sutha; Saratale, Ganesh D.; Pugazhendhi, Arivalagan; Arvindnarayan, Sundaram; Periyasamy, Sivagurunathan; Kumar, Gopalakrishnan; Kim, Sang-Hyoun
Abstract: Dark bioH2 fermentation from microalgae is a propitious technology to reduce the global CO2 emission and environmental pollution problems. This review provides the wide varieties of microalgal biomass available in the environment and also analyses the relevant studies focused on the microalgal biomass to bioH2 fermentation pathway. In this review, major enzymes and metabolic pathways involved in the dark fermentative hydrogen production has been reported. Major enzymes involved in the process are hydrogenases (FeFe and NiFe), besides, their thermo-tolerance and other aspects have been discussed. Metabolic and mechanistic pathway like acetate, butyrate (hydrogen accelerating reactions) and propionate (hydrogen consuming reactions) were highlighted. Recently microalgal biofuels along with bio refinery approach has been put forth as propitious technology for the future to solve the looming energy crisis. Major drawback in the extraction of sugars and other organic constituents from the microalgal cells are limiting their applications in various fields including bioenergy. A wide range of pretreatment methods has been applied so far and every treatment has their unique features. This report analyzes a comparative assessment of the pretreatment technologies and provides the key insights. Highlights: This review focused on the generation of biohydrogen from microalgae. Key issues affecting H2 production via dark fermentation are presented. Discussed various pretreatment strategies for sugar recovery from microalgae biomass.